Recent Advances of Silver-Based Coordination Polymers on Antibacterial Applications - Wenfeng Zhang; Gaomin Ye; Donghui Liao; Xuelin Chen; Chengyu Lu; Alireza Nezamzadeh-Ejhieh; M. Shahnawaz Khan; Jianqiang Liu; Ying Pan; Zhong Dai (Molecules, 2022)
With the continuous evolution of bacteria and the constant use of traditional antibiotics, the emergence of drug-resistant bacteria and super viruses has attracted worldwide attention. Antimicrobial therapy has become the most popular and important research field at present. Coordination Polymer (CP) and/or metal-organic framework (MOF) platforms have the advantages of a high biocompatibility, biodegradability, and non-toxicity, have a great antibacterial potential and have been widely used in antibacterial treatment. This paper reviewed the mechanism and antibacterial effect of three typical MOFs (pure Ag-MOFs, hybrid Ag-MOFs, and Ag-containing-polymer @MOFs) in silver-based coordination polymers. At the same time, the existing shortcomings and future views are briefly discussed. The study on the antibacterial efficacy and mechanism of Ag-MOFs can provide a better basis for its clinical application and, meanwhile, open up a novel strategy for the preparation of more advanced Ag-contained materials with antibacterial characteristics.